Analisa Potensi Aliran Lahar Kali Putih, Gunungapi Kelud - Hayu Rahayu; Suharyanto Suharyanto; Sri Sangkawati (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
Kelud Volcano is one of the active volcanoes and located in East Java. After the eruption, Kelud Volcano left a number of volcanic materials from the rock, sand and the ash on residential land, plantations and the surrounding area. The main problem is the eruption of Kelud Volcanoes has the potential to experience an increase in the frequency of eruptions and there has been no development of a regional reconstruction model for secondary impacts due to eruptions in the field of water resources infrastructure. Based on these problems, a test of the Sabo and modular hydraulic physical models will be planned. This study discusses the identification of the location and volume of sediments that have the potential to become Kali Putih lava flows from Kelud Volcanoes. The Takahashi analysis method is used to analyze the estimated excess volume of the target sediment which must be controlled by sabo technology. Identification of sediment transport zones is obtained from the classification of slope on existing buildings obtained from satellite imagery. The results of the analysis are as follows: 1.) Sediment transport areas in the Putih Watershed have an area of 863 km2. 2.) The total volume of Kali Putih sediment that has the potential to become cold lava after the eruption is 4,139,414.23 m3. 3.) Sabo and modular hydraulic physical model testing is required. 4) A model of regional reconstruction is needed for secondary impacts due to eruptions in the water resources field. 5) New sabo plan planning is needed